Application of physiologically active substances by culturing Hosta in Bashkortostan - Миронова, Л. Н.; Реут, А. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The effect of growth regulators (Biodux, Energen, Immunotcytofit) on the productivity of some representatives of the genus Hosta (Hosta albo-marginata, H. fortunei, H. lancifolia, H. plantaginea, H. sieboldiana, H. glauca var. aurea-variegata, H. undulata) cultured in the Bashkir Urals, was studied in field experiments. It was shown that the investigated growth regulators possess species specific effect. The most effective agent is Biodux, the most responsive species – H. glauca var. aurea-variegata and H. plantaginea.